Magnesium sulfate versus Lidocaine pretreatment for prevention of pain on etomidate injection: A randomized, double-blinded placebo controlled trial - Mohammadreza Safavi; Azim Honarmand; Ashraf Sadat Sahafi; Seyyed Mohammad Sahafi; Mohammadali Attari; Mahsa Payandeh; Alireza Iazdani; Nilofarsaddat Norian (Wolters Kluwer Medknow Publications, 2015)
Objective: Etomidate is an imidazole derivative and formulated in 35% propylene glycol. When given without a rapid lidocaine injection, etomidate is associated with pain after injection. Magnesium (Mg) is a calcium channel blocker and influences the N-methyl-D-aspartate receptor ion channel. The aim of the study is to evaluate the efficiency of preemptive injection of magnesium sulfate and lidocaine on pain alleviation on etomidate intravenous injection. Methods: In a randomized, double-blinded trial study, 135 adult patients scheduled for elective outpatient or inpatient surgery were divided into three groups. Group M received 620 mg magnesium sulfate, Group L received 3 ml lidocaine 1% and Group S received normal saline, all in a volume of 5 mL followed by a maximal dose of 0.3 mg/kg of 1% etomidate. Pain was assessed on a four-point scale: 0 = no pain, 1 = mild pain, 2 = moderate pain and 3 = severe pain at the time of pretreatment and etomidate injection. Findings: About 60% of patients in the control group had pain during etomidate injection as compared to 22.2% and 40% in the lidocaine and magnesium sulfate groups, respectively. There was difference in induction pain score between three treatment groups, significantly (P = 0.01) and observed differences in pain scores between "normal saline and lidocaine group" (P < 0.001) and "normal saline and magnesium sulfate groups" were statistically meaningful (P = 0.044). Conclusion: Intravenous magnesium sulfate and lidocaine injection are comparably effective in reducing etomidate-induced pain.